Kaiser Permanente National Total Joint Replacement Registry: aligning operations with information technology. - Paxton EW; Inacio MC; Khatod M; Yue EJ; Namba RS; Paxton, Elizabeth W; Inacio, Maria C S; Khatod, Monti; Yue, Eric J; Namba, Robert S (Clinical Orthopaedics & Related Research®, 2010)
Background: A Total Joint Replacement Registry was developed in a large community-based practice to track implant utilization, monitor revisions and complications, identify patients during recalls and advisories, and provide feedback on clinical practices.Questions/purposes: We describe the development, implementation, and integration of this Total Joint Replacement Registry, highlighting critical steps in aligning information technology and operations.Methods: The primary Total Joint Replacement Registry data source consists of standardized electronic health record forms developed by consensus. The Total Joint Replacement Registry forms are integrated into the clinical workflow (preoperative, intraoperative, and postoperative) and produce a standardized progress note for electronic health record documentation. Secondary data are extracted from other electronic data sources using standard terminologies (ie, ICD-9 codes) to supplement the Total Joint Replacement Registry forms. Electronic screening algorithms are applied to identify complications, in combination with chart review validation and quality control mechanisms.Results: Three hundred fifty surgeons voluntarily contribute to the registry with 90% participation. The registry has been used for implant recalls and advisories, contract decision making, and identification of patients at risk for revisions (eg, younger patients having total knee arthroplasty). Tracking of overall survival of implants influenced clinical practice, with feedback resulting in the reduction of the number of unicompartmental and uncemented knee arthroplasties performed, usage of femoral head sizes < 28 mm, and the number of minimally invasive surgical procedures performed.Conclusions: The Total Joint Replacement Registry has effectively aligned operations with information technology and leveraged that to enhance our ability to respond to recalls and advisories as well as improve quality of care, cost-effectiveness, and create research opportunities.